Genome analysis of Pseudomonas species reveals that Pseudomonas panacis Park et al. 2005 is a later heterotypic synonym of Pseudomonas marginalis (Brown 1918) Stevens 1925 (Approved Lists 1980). Issue 5 (4th May 2022) - Kujur, Ritu Rani Archana; Deb, Sushanta; Das, Subrata K.
Abstract : We described the comparative genomic analysis of Pseudomonas panacis DSM 18529 T and Pseudomonas marginalis DSM 13124 T of the genus Pseudomonas to define the taxonomic assignment. When conducting this analysis, genomic information for 203 type strains was available in the NCBI genome database. The ANI, AAI and is DDH data were higher than the threshold values between Pseudomonas panacis DSM 18529 T and Pseudomonas marginalis DSM 13124 T . Whole-genome comparisons show 97 % average nucleotide identity, 98 % average amino acid identity and 75 % in silico DNA–DNA hybridization values. Pseudomonas marginalis (Brown 1918) Stevens 1925 (Approved Lists 1980) have priority over the name Pseudomonas panacis Park et al . 2005, therefore nomenclatural authorities propose that Pseudomonas panacis Park et al . 2005 is a later heterotypic synonym of Pseudomonas marginalis (Brown 1918) Stevens 1925 (Approved Lists 1980). The type strain is ATCC 10844 T (=DSM 13124 T =NCPPB 667 T ).